Correlation between serum 25(OH)D levels with severity of work-related hand eczema among healthcare workers: a cross-sectional study - Danny Surya; Melani Marissa; Windy Keumala Budianti; Rahadi Rihatmadja; Inge Ade Krisanti; Dewi Friska; Sandra Widaty (PAGEPress Publications, 2023)
Background. Hand eczema (HE) commonly occurs in healthcare services, especially during COVID-19 pandemic era. Vitamin D shows various effects on skin inflammation. This study aims to analyze the correlation between HE severity and vitamin D levels as measured by serum 25(OH)D in healthcare workers. Method. This is an analytic descriptive study with a cross-sectional design conducted in Indonesia between September-October 2022. HE severity was assessed using Hand Eczema Severity Index (HECSI). Results. Among 44 healthcare workers with HE, 29 people had mild HE, 11 had moderate HE, and 4 had severe HE. The mean serum 25(OH)D level in subjects with mild, moderate, and severe HE was 17.85 ng/mL, 16.45 ng/mL, and 17.87 ng/mL, respectively, which belonged to vitamin D deficiency category. There was no statistically significant correlation between serum 25(OH)D levels and HE severity (r = -0.056; p = 0.359). Conclusions. There was no significant difference in serum 25(OH)D levels between subjects with mild, moderate, and severe HE. Serum 25(OH)D level was not inversely correlated with HE severity.